Analysis of Fery Irwandi's Persuasive Communication Style in Exposing Santet and Indigo Lies within Indonesian Cultural Beliefs - M. Ibnu Naufal Maskuri; Ali Ridho; Fitri Yanti; Ade Nur Istiani (Kalijaga Journal of Communication, 2026)
This study analyzes Fery Irwandi's persuasive communication style in the video "Dismantling the Lies of Santet and Indigo," focusing on message delivery strategies, communicator credibility, and audience response. The research aims to understand how persuasive communication can be used to dismantle myths and irrational beliefs that remain entrenched in society. The method used is qualitative, with a content analysis approach, based on in-depth observation of the verbal and nonverbal content displayed in the video. The study's results show that Fery Irwandi uses a combination of rational and emotional strategies to convey messages. Rationally, he emphasized the importance of critical thinking and of proving, through simple logic, the unsubstantiated claims of Santet and Indigo. Emotionally, he stirs the audience's feelings by highlighting the negative effects of mystical beliefs, such as social fear, conflict, and deception. The communicator's credibility is strengthened by serious expression, firm intonation, and consistent argument, making the message more trustworthy. The findings of this study are in line with persuasive communication theory, which emphasizes the importance of integrating rational, emotional, and credibility factors with the audience. In conclusion, effective persuasive communication not only conveys arguments but also builds critical literacy and encourages changes in people's mindsets.